Association of COVID-19 infection and COVID-19 vaccination with idiopathic sudden sensorineural hearing loss in Malaysia: a case-control study - Nur Sabrina Abdul Rahim; Xin-Jie Lim; E-Li Leong; Su-Yin Lim; Nur Azyani Amri; Chee Chean Lim; Philip Rajan Devesahayam; Jawatankuasa Teknikal Audiologi (JKTA); ORL Working Group (BMC Public Health)
Abstract Background Previous studies indicated that the SARS-CoV-2 virus and COVID-19 vaccines may contribute to idiopathic sudden sensorineural hearing loss (ISSNHL). This nationwide study sought to evaluate the correlation between COVID-19 infection and vaccination with ISSNHL. Methods This case–control study analysed samples from adults aged 18 years and older who visited the otorhinolaryngology department in 32 government hospitals in Malaysia for pure tone audiometry(PTA) between January 25, 2020 and June 30, 2022. Cases comprised patients diagnosed with ISSNHL, while controls consisted of individuals with normal PTA assessments presenting for other otorhinolaryngology-related symptoms during the same period. Patients with known causes of hearing loss were excluded. Cases and controls were matched in a 1:5 ratio based on age (± 5 years) and index date (± 10 days). The study investigated the association between ISSNHL and both COVID-19 vaccination and COVID-19 infection using conditional logistic regression, with statistical significance set at P < 0.05 for two-sided tests. Results A total of 187 ISSNHL cases and 935 matched controls were included. The mean (SD) age of participants was 42.4 (12.3) years, and 704 (62.7%) were female. Cases had a higher proportion of COVID-19 infections compared to controls [16 (8.6%) vs 44 (4.7%), P = 0.034], while both groups had similar proportions of COVID-19 vaccination [90 (48.1%) vs 415 (44.5%), P = 0.377]. Individuals who tested positive for COVID-19 had a significantly higher likelihood of developing ISSNHL compared to those without COVID-19 infection at the time of diagnosis (aOR:2.49; 95% CI:1.176 – 5.260; P = 0.017). However, there was no statistically significant association between COVID-19 vaccination and ISSNHL. Conclusions This study provides significant insights into the intricate correlation between ISSNHL, COVID-19 infection, and vaccination. The recognized hazard linked to infection emphasizes the significance of monitoring auditory health in COVID-19 patients.